1977
DOI: 10.1007/bf01257017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estrogen on prolactin and tuberoinfundibular dopaminergic neurons

Abstract: Serum prolactin concentrations and dopamine turnover in the striatum and median eminence were studied in male rats after the administration of estradiol benzoate. The alpha-methyltyrosine-induced reduction of dopamine concentrations in these brain regions was used to evaluate relative rates of turnover. Steady state dopamine concentrations in the median eminence and striatum were not altered by 1, 3 or 5 days of estradiol treatment. However, 3 or 5 days of estradiol administration enhanced dopamine turnover in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
0

Year Published

1979
1979
1991
1991

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(39 citation statements)
references
References 16 publications
6
33
0
Order By: Relevance
“…Eikenburg et al (1977) showed in rats that treatment for 5 days with oestrogen resulted in approximately threefold increases in serum prolactin and increased DA turnover in the median eminence but no changes were seen in DA concentrations. The study of Eikenburg et al (1977) did not investigate the effects of chronic hyperprolactinaemia in the situation when prolactin-secreting tumours are present and the degree of hyperprolactinaemia is great. After chronic (3 months) treatment with oestradiol valerate in the rat prolactin-secreting pituitary tumours are seen associated with specific pathological changes in the hypothalamus (Brawer and Sonnenschein 1975;Brawer and Naftolin 1979).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eikenburg et al (1977) showed in rats that treatment for 5 days with oestrogen resulted in approximately threefold increases in serum prolactin and increased DA turnover in the median eminence but no changes were seen in DA concentrations. The study of Eikenburg et al (1977) did not investigate the effects of chronic hyperprolactinaemia in the situation when prolactin-secreting tumours are present and the degree of hyperprolactinaemia is great. After chronic (3 months) treatment with oestradiol valerate in the rat prolactin-secreting pituitary tumours are seen associated with specific pathological changes in the hypothalamus (Brawer and Sonnenschein 1975;Brawer and Naftolin 1979).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been proposed that central serotoninergic neurones mediate the effect of oestrogen on prolactin release (Caligaris and Taleisnil( 1974). Oestrogen administration depresses 'prolactin-inhibiting factor' activity in the rat hypothalamus (Ratner and Meites 1964) and since prolactin release is tonically inhibited via hypothalamic dopamine (DA) pathways which have been shown to be subject to negative feedback by prolactin, attention has recently been directed toward the role of DA in oestrogen-induced hyperprolactinaemia (Eikenburg et al 1977). Eikenburg et al (1977) showed in rats that treatment for 5 days with oestrogen resulted in approximately threefold increases in serum prolactin and increased DA turnover in the median eminence but no changes were seen in DA concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially (after approximately 3 days) this results in the maintenance of basal serum prolactin levels near normal but there is an enhanced prolactin response to DA synthesis inhibition relative to controls (Eikenburg·et al 1977). However, as the E2 stimulus and lactotroph hyperplasia maintain the drive to release more prolactin, we suggest that a limit to hypothalamic DA activity is reached after which serum prolactin levels cannot be kept near normal.…”
Section: Discussionmentioning
confidence: 87%
“…In the short term, at least, the administration of exogenous prolactin or the induction of high levels of prolactin secretion in the rat result in increased dopamine (DA) turnover in the median eminence without altering steady-state concentrations of DA (GudeIsky et al 1976;Eikenburg et al 1977). When circulating prolactin levels are raised in the rat 3-5 days following oestrogen (E 2 ) administration there is a significant increase in median eminence DA turnover and an increased prolactin release from the pituitary in response to tyrosine hydroxylase inhibition with IX-methyl-tyrosine (Eikenburg et al 1977). However, we have recently presented evidence that this initial response to increased prolactin secretion is not maintained following chronic hyperprolactinaemia induced by E2 treatment in the rat (Smythe and Brandstater 1980).…”
Section: Introductionmentioning
confidence: 99%